Asthma: the role of low high-density-lipoprotein cholesterol in childhood and adolescence - Yiallouros, Panayiotis K.; Savva, Savvas C.; Kolokotroni, Ourania; Dima, Kleanthi; Zerva, Aikaterini; Kouis, Panagiotis; Bousquet, Jean J.; Middleton, Nicos (My University, 2014)
Background: Several studies have examined the relationship of asthma with serum dyslipidemia and reported positive, negative or no association. Most studies were limited by their cross-sectional design and the wide age range of the participants. In a cohort of children in Cyprus, we explored the association of asthma with serum high-density-lipoprotein cholesterol (HDL-C) at age 16-18 years (follow-up) independently of and in relation to HDL-C at age 11-12 years (baseline). Methods: In a case-control design, we recruited active asthmatics (AA; n = 68), current wheezers only (CWO; n = 123) and non-asthmatic controls (n = 660). Logistic regression models were used to evaluate associations of asthma with follow-up serum HDL-C and the role of baseline HDL-C. Results: At follow-up, mean HDL-C levels in AA and CWO patients were significantly lower than in the controls (47.9 and 49.7 vs. 53.4 mg/dl; p = 0.001 and p = 0.011). We observed significant associations of AA patients with low HDL-C (<15th percentile; OR 2.32, 95% CI 1.16-4.47) that remained significant after further adjustment for baseline HDL-C (OR 2.14, 95% CI 1.06-4.14). Stratification by baseline HDL-C indicated that the association was significant only in those with high baseline HDL-C (OR 2.40, 95% CI 1.03-5.20). Stratification by IgE sensitization showed that the association was pronounced only in subjects who were sensitized (OR 3.41, 95% CI 1.12-9.88). Conclusions: Adolescent asthma is associated with low serum HDL-C independent of previous HDL-C levels in childhood. The association appears pronounced in those with a drop in HDL-C levels between childhood and adolescence and in those who have IgE sensitization.
Keywords: Asthma; Childhood; Lipid transfer protein; Pediatric allergy